Trade Union Advisory Medical Officers - Morgan, H. B. (Hyacinth Bernard Wenceslaus Morgan), 1885-1956
1920 1920 1920s 9 pages Confidential TRADE UNION ADVISORY MEDICAL OFFICERS by Dr. H.B. Morgan, 38 Albert Palace Mansions, Battersea Park, S.W. A memorandum suggesting the desirability of the appointment of an Advisory Medical Officer to the Headquarters of each Trade Union of the workers has already been submitted. A few copies have been circulated confidentially to a few selected Trade Unions and it is believed that the subject is receiving the favourable consideration of their respective Executives. A copy of the first Memorandum is submitted herewith. It will be noticed that ways and means are suggested so as to bring the scheme within the scope and power of even the smallest Union. It is recognised that many of the details of any particular scheme as affecting any particular Trade Union will require prolonged consideration and discussion. And the main scheme should be elastic so as to be capable of modification, and to fit it later into the Medical Division of the General Staff of the Labour Movement. And it may take some time for even the main central idea to be grasped and fully appreciated. Some Trade Unions, or their executives or officials may look askance at an innovation which so far in the history of Trade Unionism has been done without. But if the possibilities of the idea and the possible resultant benefits not only to individual members of the national organisations, but to the Labour Movement as a whole be kept in mind, the issue is confidently submitted as sure of adoption in the long run. The question of a medical section to the Labour movement may be considered from three aspects:- (1) That of the individual member of a Trade Union. (2) That of a particular Trade Union. (3) That of the section as part of the scheme for a General Staff of the Labour Movement. And the medical work of the Labour Movement may be considered from 2 points of view. (a) The clinical work - the examination of each particular patient or case. (b) The advisory work. It is on the advisory aspect that the observations in this memorandum tend to be concentrated. It is realised that especially in the initial stages of the adoption of the idea that the Medical Officer of any particular Trade Union will have not only advisory functions, but also important clinical work. In some cases, one or other aspect may predominate, depending on the nature of the Trade organisation and the nature of the employment of its members. And if the idea be adopted, the first Medical Officers will have to be prepared and to be able to do both clinical work and give the necessary advice. Later on, the separation between the Advisory Medical Staff and those medical men actually engaged in the clinical work will be more marked. Too much should not be expected of the scheme in its initial stages, but with the growing clinical experience and true insight into the right mode of presentation of advice suitable to particular Unions or the Movement as a whole, the Advisory Medical Officer or Officers will be able to take up the cudgels for Labour with the status of his office, and the knowledge of the great cause represented. INDIVIDUAL TRADE UNIONISTS. As individuals, Trade Unionists share in the disabilities of the present system of medical service and of hospital administration. The main idea is through the Trade Union Movement by the appointment of special Trade Union medical officials, to secure for the country as a whole a better medical service both under the present conditions and in a changed society, to enable the Labour movement to 36/H24/11